2010
DOI: 10.1182/blood-2009-10-233585
|View full text |Cite
|
Sign up to set email alerts
|

NFAT pulls the strings during CD4+ T helper cell effector functions

Abstract: The Ca 2؉ dependent transcription factor family known as nuclear factor of activated T cells (NFAT) has been shown to be important in T-cell immune responses. Because NFAT proteins have a weak DNAbinding capacity, they cooperate with other transcription factors at composite sites within the promoters of target genes. Recently, NFAT was shown to also be important for the induction of specific genetic programs that guide the differentiation and effector or regulatory activities of CD4 ؉ T helper subsets via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(179 citation statements)
references
References 101 publications
3
171
0
5
Order By: Relevance
“…However, in this study we found no impact of NFAT inhibition on bacterial burden in blood, peritoneal cavity, lung, and spleen 24 h after CLP induction. In this context, it is important to note that NFAT has been well established as a promoter of T-cell maturation and differentiation (54). At first glance, our findings showing that inhibition of NFAT protects T-cell survival and cytokine formation might appear counterintuitive.…”
Section: Discussionmentioning
confidence: 63%
“…However, in this study we found no impact of NFAT inhibition on bacterial burden in blood, peritoneal cavity, lung, and spleen 24 h after CLP induction. In this context, it is important to note that NFAT has been well established as a promoter of T-cell maturation and differentiation (54). At first glance, our findings showing that inhibition of NFAT protects T-cell survival and cytokine formation might appear counterintuitive.…”
Section: Discussionmentioning
confidence: 63%
“…2A). The results are counterintuitive because NFAT and IRF have been shown to synergize with each other in regulating in gene expression, and the two binding sites are partially overlapped at the nucleotide level (6,10). This prompted us to determine the enrichment of the IRF1 binding site at the promoter region (Ϫ10 to 2 kb around the transcription start site) of up-and downregulated genes in WT and null cells.…”
Section: High Nacl Alters Expression Of Very Few Genes In Common Betwmentioning
confidence: 97%
“…However, in response to 18% CS, reductions in STAT5 expression significantly attenuated SNP-dependent enhanced NAMPT promoter activity with either NAMPT variant. Because GR acts as a transcriptional coactivator for STAT5 and enhances STAT5-dependent transcription (32) and because STAT5 combines with nuclear factor of activated T cells to promote Foxp3 transcription (33), the effects of the 2948G/T and 22,422A/G SNPs may synergize with STAT5 to significantly enhance NAMPT transcription with the influence of these cotranscription factors during pathological stress. Together, these studies demonstrated that STAT5 significantly regulates NAMPT transcription under pathological mechanical stress.…”
Section: Discussionmentioning
confidence: 99%